The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1sm00621e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dielectric elastomers to develop materials suitable for actuation

Abstract: Commercial dielectric elastomers and their modification methods are reviewed. A method is proposed to overcome the complex interdependency of their properties allowing quick comparison and selection of suitable materials for soft actuator applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…1 The current commercial elastomers such as silicone and VHB have low relative permittivity (ε′, 2∼4), showing limited energy transduction efficiency when used for actuators and energy generators. 2 In addition, commercial elastomers are often produced by covalently crosslinking or vulcanizing to form permanent covalent cross-linking networks for enhanced mechanical robustness and chemical resistivity. However, the permanent cross-linked elastomers raised further challenges in repairing, reprocessing, or recycling, which highly limit the sustainable applications of the DEs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The current commercial elastomers such as silicone and VHB have low relative permittivity (ε′, 2∼4), showing limited energy transduction efficiency when used for actuators and energy generators. 2 In addition, commercial elastomers are often produced by covalently crosslinking or vulcanizing to form permanent covalent cross-linking networks for enhanced mechanical robustness and chemical resistivity. However, the permanent cross-linked elastomers raised further challenges in repairing, reprocessing, or recycling, which highly limit the sustainable applications of the DEs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The energy transduction performance of DEs is intrinsically determined by the dielectric permittivity, electrical breakdown strength, and mechanical stretchability of the elastomers . The current commercial elastomers such as silicone and VHB have low relative permittivity (ε′, 2∼4), showing limited energy transduction efficiency when used for actuators and energy generators . In addition, commercial elastomers are often produced by covalently crosslinking or vulcanizing to form permanent covalent cross-linking networks for enhanced mechanical robustness and chemical resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the last decade have reported that dielectric elastomers are very promising materials to convert electrical energy into mechanical energy, or vice versa, in several applications, such as electromechanical transducers or energy-harvesting systems [ 1 , 9 , 10 , 11 ]. All these studies have had as their final goal to improve the electromechanical sensitivity of the dielectric elastomers through several approaches, such as testing different types and combinations of polymers, with or without adding (nano)particles to make dielectric composites [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the last decade have reported that dielectric elastomers are very promising materials to convert electrical energy into mechanical energy, or vice versa, in several applications, such as electromechanical transducers or energy-harvesting systems [ 1 , 9 , 10 , 11 ]. All these studies have had as their final goal to improve the electromechanical sensitivity of the dielectric elastomers through several approaches, such as testing different types and combinations of polymers, with or without adding (nano)particles to make dielectric composites [ 11 ]. However, what material property needs to be changed to improve its actuation performance and which figure of merit is best to evaluate the electromechanical conversion abilities of the tested dielectric elastomers are two questions with different answers based on the different approaches reported in the literature [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A dielectric elastomer (DE) refers is a novel intelligent material that is capable of producing large shape and size deformation under an external electric field [ 1 , 2 , 3 , 4 ]. Compared with conventional intelligent materials (e.g., shape memory alloys (SMAs), piezoelectric ceramic (PZT), and magnetostrictive material (MSM), DE materials have shown advantages of a fast response, large electrical distortion, good elasticity, high efficiency of electromechanical transformation, etc.…”
Section: Introductionmentioning
confidence: 99%